The overlapping of phenotypes in Wiedemann-Steiner, Kleefstra and Coffin-Siris syndromes: a study of eleven patients - Elisabetta Prada; Camilla Meossi; Denise Piras Marafon; Federico Grilli; Giulietta Scuvera; Paola Giovanna Marchisio; Carlo Virginio Agostoni; Federica Natacci; Donatella Milani (BMC, 2024)
Abstract Background Some chromatinopathies may present with common clinical findings (intellectual disability, brain and limb malformation, facial dysmorphism). Furthermore, one of their cardinal shared features is growth dysregulation.We aimed to assess and deepen this resemblance in three specific conditions, namely Wiedemann-Steiner (WDSTS), Kleefstra (KLEFS1) and Coffin-Siris syndrome (CSS1), with a particular focus on possible metabolic roots. Methods Eleven patients were enrolled, three with WDSTS, five with KLEFS1 and three with CSS1, referring to Fondazione IRCCS Ca' Granda Ospedale Maggiore, Milan, Italy. We performed both a physical examination with detailed anthropometric measurements and an evaluation of the patients' REE (rest energy expenditure) by indirect calorimetry, comparing the results with age- and sex-matched healthy controls. Results We observed new clinical features and overlap between these conditions suggesting that different disturbances of epigenetic machinery genes can converge on a common effect, leading to overlapping clinical phenotypes. The REE was not distinguishable between the three conditions and healthy controls. Conclusions Epigenetic machinery plays an essential role both in growth regulation and in neurodevelopment; we recommend evaluating skeletal [craniovertebral junction abnormalities (CVJ) polydactyly], otolaryngological [obstructive sleep apnea syndrome (OSAs), recurrent otitis media], dental [tooth agenesis, talon cusps], and central nervous system (CNS) [olfactory bulbs and cerebellum anomalies] features. These features could be included in monitoring guidelines. Further studies are needed to deepen the knowledge about energy metabolism.